Rancang Bangun Remotely Operated Vehicle (ROV) untuk Monitoring Kondisi Terumbu Karang di Perairan Bontang - Musa Payung; Abdul Zain (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2021)
Coral reefs and all the life in them are one of the natural resources owned by the Indonesian people that are invaluable. Bontang city, located in East Kalimantan, is dominated by the ocean. Observation of the condition of coral reefs has been carried out by diving (diving) or snorkeling. For certain conditions, such as difficult locations, it does not allow humans to dive and observe directly the condition of coral reefs. This study proposes an alternative observation of coral reefs in Bontang waters using ROV. ROV is an underwater explorer robot controlled by an operator with a control device. The ROV in this study uses the arduino mega2560 as a controller, the BTS7960 module as a motor driver, MS5540CM sensor, motor as a driver. The ROV is equipped with a camera to take pictures and display them on a monitor. The results show that the ROV can work in the water, the ROV movement can be controlled and can maneuver well. ROV can automatically maintain depth when not operated with a range of ± 5 cm. The camera video system works well. The image captured by the camera can be displayed on the monitor in realtime. From the test results, it was found that the delay was less than 1 second between the image captured by the camera and the image displayed.